Bifunctional electrolyte additive KI to improve the cycling performance of Li–O2 batteries. (1st October 2018) - Li, Changjin; Qian, Zhengyi; Ma, Yulin; Zuo, Pengjian; Du, Chunyu; Huo, Hua; Yin, Geping
Abstract : Bifunctional electrolyte additive KI could effectively inhibit lithium dendrite growth and reduce the charge overpotential simultaneously. Abstract : Non-aqueous rechargeable Li–O2 batteries have attracted great attention owing to their ultra-high specific energy densities. However, the high charge overpotential and the interfacial instability of lithium anodes still need to be overcome before the practical application of Li–O2 batteries. Here, we use KI as a bifunctional electrolyte additive for Li–O2 batteries. The results demonstrate that I − could act as a redox mediator to effectively reduce the charge overpotential by 0.7 V. On the other hand, the introduction of K + contributes to decreasing the polarization, optimizing the morphology, reducing the surface by-products of the lithium anode and dramatically improving the uniform distribution of discharge products on the cathode surface. The dual functions of KI additive thus successfully boost the electrochemical performances of Li–O2 batteries.